U.S. Banking Deregulation, Small Businesses, and Interstate Insurance of Personal Income - DEMYANYK, YULIYA; OSTERGAARD, CHARLOTTE; SØRENSEN, BENT E. (Journal of Finance, 2007)
ABSTRACT We estimate the effects of deregulation of U.S. banking restrictions on interstate personal income insurance for the period 1970 to 2001. Interstate income insurance occurs when personal income reacts less than one‐to‐one to state‐specific output shocks. We find that insurance improved after banking deregulation, with a larger effect in states where small businesses are more important and on proprietors' income than on other components of personal income. Our explanation centers on the role of banks as a prime source of small business finance and on the close intertwining of the personal and business finances of small business owners.